CDK5-mediated hyperphosphorylation of Tau217 impairs neuronal synaptic structure and exacerbates cognitive impairment in Alzheimer’s disease - Kangyue Fu; Nan Lin; Yiwen Xu; En Huang; Raoli He; Zhixin Wu; Dianbo Qu; Xiaochun Chen; Tianwen Huang (Translational Psychiatry)
Abstract Numerous studies have demonstrated that tau phosphorylated at threonine 217 (p-T217) in cerebrospinal fluid (CSF) or plasma is a potential biomarker for Alzheimer’s disease (AD). However, the detailed pathological effects of elevated p-T217 and the mechanisms underlying T217 phosphorylation remain incompletely understood. In this study, we revealed a role of tau phosphorylated at T217 in AD. In 5 × FAD mice, increased p-T217 levels, correlated with CDK5 activation, were associated with neurite damage and neuronal apoptosis. Mice expressing a phospho-mimetic T217E mutant in the hippocampus exhibited significant learning impairments in the Morris water maze and Y-Maze test, along with reduced levels of the synaptic proteins Drebrin and PSD95. Electron microscopy revealed severe synaptic and microtubules damage in these mice, along with disrupted axonal structures confirmed by Golgi staining. Additionally, hyperactivation of CDK5 through p25 overexpression increased T217 phosphorylation, whereas CDK5 inactivation reduced it. The study concludes that CDK5 mediated Tau phosphorylation at T217 contributes to synaptic damage and cognitive deficits, highlighting it as a potential therapeutic target for AD.